The heterogeneous effect of carbon emissions, renewable energy consumption, and urbanization in MINT countries: Evidence from panel quantile regression - Herve, Drama Bedi Guy (Asian Development Policy Review, 2025)
This study examines the relationships between CO2 emissions, renewable energy consumption, and urbanization in MINT countries (Mexico, Indonesia, Nigeria, Turkey) from 1990 to 2021. Using World Development Indicator data, we conducted cross-section dependence testing, first-generation unit root tests confirming stationarity in the first difference, cointegration analysis, and panel quantile regression to address heterogeneity and outliers. Carbon emissions are negatively influenced by urban population and renewable energy consumption, except at the highest urban population quantiles. Renewable energy consumption is negatively affected by carbon emissions and urban living standards. Carbon emissions positively impact urbanization at lower quantiles but negatively at medium/high quantiles. Renewable energy consumption consistently shows negative effects on urbanization across all quantiles. Complex, quantile-dependent relationships exist between variables, with significant variations across distribution levels in MINT countries. Governments should implement fiscal incentives promoting renewable energy technology adoption as alternatives to fossil fuels, enhancing affordability for urban populations while improving environmental quality.